The Potential of Flexible Heating for Multi-Family Houses in Sweden - Kleinschmidt, Per; Söderlind, Ida (Chalmers tekniska högskola / Institutionen för rymd-, geo- och miljövetenskap, 2024)
The residential and services sector accounted for a significant portion (39%) of the final energy consumption in 2020 in Sweden, with district heating (DH) and elec tricity as the main heating sources. The choice of heating source varies throughout different types of buildings, and the most common for multi-family houses in Sweden is DH. When moving towards an energy system with a larger share of renewables, which includes irregularity of production, a flexible demand of electricity will be important to maintain the balance between production and consumption in the power system. This thesis aims to investigate the potential of flexible heating for multi-family houses in Sweden. The investigation has been made by a model structured in GAMS by using mixed-integer linear programming, to optimize the heating pattern and the installed capacity, with the aim of minimizing the total annual cost (including in vestment, operational, and maintenance costs). The robustness of the model and results have been assessed by adjusting the input data, such as the district heating power and energy price, the electricity grid price, and the heat pump (HP) lifetime. The scope of the thesis was to investigate the potential of flexible heating in dif ferent regions of Sweden. Luleå, Sundsvall, Gothenburg, and Malmö have been investigated due to their geographical location as they are located in different elec tricity zones. The study focused on two buildings built in different eras. This comparison aimed to highlight the differences in results based on the different building characteristics. The thesis is in collaboration together with Riksbyggen (Swedish housing company), which provided the data for the buildings involved in the study. The results indicate that flexible heating in multi-family houses in Sweden is econom ical favorable. A wider accepted indoor temperature range (19°C - 25°C) decreases the total heating demand, the necessary installed capacity and the total cost up to 14% compared with a non-flexible indoor temperature ...